Determinants of anti-money laundering system’s effectiveness in Ukraine: Insights from factorial and regression analysis - Dariusz Krawczyk; Gulnara Zhanseitova; Oleksii Zakharkin; Maksym Zhytar; Tetiana Dotsenko; Ievgenii Vovk; Tetiana Vasylieva (Public and Municipal Finance)
The effectiveness of anti-money laundering systems is vital for national economic resilience, especially in transitional economies facing wartime challenges, such as Ukraine. This study aims to identify key managerial determinants of the effectiveness of Ukraine’s anti-money laundering and counter-terrorist financing (AML/CFT) system and to develop evidence-based recommendations for improving its performance. Based on data from Ukrainian national institutions for the period 2011–2023, the study employs principal component analysis and multiple linear regression to evaluate 44 statistical indicators related to institutional workload, procedural efficiency, and inter-agency coordination. The findings reveal that a small set of indicators, including the volume of suspicious transaction reports from non-banking institutions, the number of dossiers compiled, and the backlog of unresolved judicial cases, explain over 70% of the system’s output variance. The final model exhibits high explanatory power (R² = 0.963), underscoring the importance of prioritizing high-impact operational metrics. The study concludes that targeted procedural reforms and enhanced coordination between institutions can significantly strengthen AML/CFT outcomes in fragile and reforming contexts. AcknowledgmentThis study was supported by the Ministry of Education and Science of Ukraine (project No. 0123U101945 – National security of Ukraine through prevention of financial fraud and money laundering: war and post-war challenges).